Electrochemical impedance spectroscopy analysis to accelerate electrocatalytic system innovation - Zhu, Hanbing; Liu, Yinghuan; Guo, Wenxin; Zheng, Jinyu; Zheng, Yao; Cherevko, Serhiy; Tang, Cheng; Zhang, Qiang (Science China-Chemistry, 2024)
Electrochemical impedance spectroscopy (EIS) is a well-established non-destructive characterization technique for assessing the efficacy of electrochemical energy storage and conversion systems. Electrocatalytic systems based on proton exchange membrane (PEM), including PEM fuel cells and PEM water electrolyzers, play a crucial role in renewable energy conversion through electricity–hydrogen interconversion. EIS, along with its derived analysis methods—equivalent circuit model (ECM), distribution of relaxation time (DRT), and dynamic EIS (DEIS), is widely utilized to extract valuable kinetics and impedance data. The acquired information affords critical insights into processes such as mass transfer, charge transfer, and proton transfer within PEM systems. This mini review surveys the role of EIS in optimizing components and investigating operational conditions to enhance the efficiency of PEM systems. In addition, it encapsulates the principles and applications of EIS-based methods like DRT and DEIS, highlighting their potential in the practical application of PEM systems.
CRIS-Team Scopus Importer:2025-02-04
Keywords: charge transfer; distribution of relaxation time; electrochemical impedance spectroscopy; proton exchange membrane water electrolyzers; reaction kinetics